Seasonality of calving in Jaffarabadi buffaloes - SN Ghodasara; KS Murthy; PU Gajbhiye; AR Ahlawat (Journal of Livestock Biodiversity, 2025)
The pattern of calving in Jaffarabadi buffaloes was analysed in an organized farm. Calving records of 616 Jaffarabadibuffaloes were used. Season and month had significant (p